Purchase Request through Epicor System in Manufacturing Company - Ely Kartikaningdyah; Agustina Agustina (Journal of Applied Accounting and Taxation, 2016)
Purchase transaction is the most often performed transaction to fulfill the needs in a company. Company’s needs shall be processed to be bought if purchase requisition for required items/services already be performed. This research aims to know the purchase requisition at sample company in terms of fulfilling the needs of the company which the procedure is carried out online through Epicor10 Environment system. Data collection methods used are interviews, direct observation, and literature reviews. Data obtained includes organizational structure, purchase requisition procedure, other various documents, and functions related to purchase requisition procedure. The result of this research shows that purchase requisition procedure applied by company has done fairly well, but there are some weaknesses in applying procedure. As for some of these weaknesses are no standards to create part number to register items or services to the system and multiple positioning causing inefficiency in purchase requisition procedure. It is recommended for the company to create clear standards, so that items or services needed can be processed easily and purchase requisition procedure is not obstructed by multi positioning.